A New Conceptual Framework for Teacher Identity Development - Pishghadam, Reza; Golzar, Jawad; Miri, Mir Abdullah (Frontiers in Psychology, 2022)
Teacher identity has evolved from a core, inner, fixed, linear construct to a dynamic, multifaceted, context-dependent, dialogical, and intrinsically related phenomenon. Since little research has provided an inclusive framework to study teacher identity construction, this article proposes a novel conceptual framework that includes the following components: mirrors of power, discourse, the imagination of reality, investment, emotioncy, and capital. The above core constituents have been discussed thoroughly to trigger significant insights about teacher identity development.